Isotopic Composition of CO2 in the Atmosphere of Mars: Fractionation by Diffusive Separation Observed by the ExoMars Trace Gas Orbiter. Issue 12 (17th December 2021) - Alday, Juan; Wilson, Colin F.; Irwin, Patrick G. J.; Trokhimovskiy, Alexander; Montmessin, Franck; Fedorova, Anna A.; Belyaev, Denis A.; Olsen, Kevin S.; Korablev, O.; Lefèvre, Franck; Braude, Ashwin S.; Baggio, Lucio; et al.
Abstract: Isotopic ratios in atmospheric CO2 are shaped by various processes throughout Mars' history, and can help understand what the atmosphere of early Mars was like to sustain liquid water on its surface. In this study, we monitor the O and C isotopic composition of CO2 between 70 and 130 km for more than half a Martian year using solar occultation observations by the Atmospheric Chemistry Suite onboard the ExoMars Trace Gas Orbiter. We find the vertical trends of the isotopic ratios to be consistent with the expectations from diffusive separation above the homopause, with average values below this altitude being consistent with Earth‐like fractionation ( δ 13 C = −3 ± 37‰; δ 18 O = −29 ± 38‰; and δ 17 O = −11 ± 41‰). Using these measurements, we estimate that at least 20%–40% of primordial C on Mars has escaped to space throughout history. The total amount of C lost from the atmosphere is likely to be well in excess of this lower limit, due to carbonate formation and further sink processes. In addition, we propose a photochemical transfer of light O from H2 O to CO2 to explain the larger enrichment in the O 18 / O 16 ^18O/^16O ratio in H2 O than in CO2 . Plain Language Summary: There is ample evidence suggesting that liquid water was abundant on the surface of Mars in the past. However, climatic conditions on early Mars must have been very different from the ones we observe today to sustain liquid water on its surface. The ratios of the heavy and light isotopes in different species provide a very useful tool to estimate the early climate of Mars. In this study, we monitor the isotopic ratios of carbon dioxide in the atmosphere of Mars to provide more accurate estimates of these. With our measurements, and in context with previous studies, we estimate that at least 20%–40% of the carbon reservoir has been lost to space throughout Martian history. This, together with the sequestration of atmospheric C on the surface in the form of minerals, is consistent with the idea that the atmosphere of early Mars was denser than the one we observe today. Key Points: Isotopic ratios in CO2 are observed to be consistent with telluric standards and to fractionate by diffusive separation above the homopause At least 20%–40% of the C reservoir has escaped to space throughout Martian history The higher 18 O/ 16 O ratio in H2 O than in CO2 may be explained by a photochemical transfer of lighter O from H2 O to CO2